An Analysis of Receptive and Productive Vocabulary Knowledge of Informatics Engineering Students at a Private University - Gusti Viranda Chorena; Pupung Purnawarman (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
Several universities in Indonesia require the use of English in some aspects of the learning process for non-English majors, especially for Informatics Engineering students. The students are required to analyse enormous amounts of English for specific or academic purposes (ESP/EAP) text throughout their learning process. Extensive vocabulary knowledge plays a very important role here, considering that they are presented with assignments in more specific contexts. The vocabulary knowledge can help students navigate the overlaps with common vocabulary but carry different contextual meanings in their field. Therefore, this research involved Informatics Engineering students at a private university with two classes, regular and non-regular, to analyse the students’ receptive and productive vocabulary sizes and to know what factors affect the sizes within a cross-sectional survey research. The data were collected by conducting a Receptive Vocabulary Size Test (RVST), a Productive Vocabulary Size Test (PVST) within the Academic and University Word List, and a set of questionnaires. The results reveal the level of the students' vocabulary sizes and the factors that affect the sizes. The implication of the research results concerning the Informatics Engineering students’ receptive and productive vocabulary sizes is discussed in this research.